2020
DOI: 10.1371/journal.ppat.1008327
|View full text |Cite
|
Sign up to set email alerts
|

Naïve CD8 T cell IFNγ responses to a vacuolar antigen are regulated by an inflammasome-independent NLRP3 pathway and Toxoplasma gondii ROP5

Abstract: Host resistance to Toxoplasma gondii relies on CD8 T cell IFNγ responses, which if modulated by the host or parasite could influence chronic infection and parasite transmission between hosts. Since host-parasite interactions that govern this response are not fully elucidated, we investigated requirements for eliciting naïve CD8 T cell IFNγ responses to a vacuolar resident antigen of T . gondii , TGD057. Naïve TGD057 antigen-specific CD8 T cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 147 publications
(320 reference statements)
4
36
0
Order By: Relevance
“…However, the role of the inflammasome is dispensable and limited when TLR11 remains functional, due to TLR11-dependent IL-12 production is sufficient to generate Th1 immunity to the parasite without inflammasome dependent release of IL-18. Furthermore, Angel K. Kongsomboonvech et al recently reported that Naïve CD8 T cell IFN-g responses to T. gondii require the inflammasome-independent NLRP3 pathway and rhoptry proteins (ROP) 5 (59). This paper was identified that the NLRP3 regulates T cell function and underscore the need for NLRP3-activating adjuvants in vaccines targeted at inducing CD8 T cell-derived IFN-g responses to T. gondii.…”
Section: Functions Of Inflammasomes In Rodent Models Of T Gondii Infectionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, the role of the inflammasome is dispensable and limited when TLR11 remains functional, due to TLR11-dependent IL-12 production is sufficient to generate Th1 immunity to the parasite without inflammasome dependent release of IL-18. Furthermore, Angel K. Kongsomboonvech et al recently reported that Naïve CD8 T cell IFN-g responses to T. gondii require the inflammasome-independent NLRP3 pathway and rhoptry proteins (ROP) 5 (59). This paper was identified that the NLRP3 regulates T cell function and underscore the need for NLRP3-activating adjuvants in vaccines targeted at inducing CD8 T cell-derived IFN-g responses to T. gondii.…”
Section: Functions Of Inflammasomes In Rodent Models Of T Gondii Infectionmentioning
confidence: 68%
“…Furthermore, Angel K. Kongsomboonvech et al. recently reported that Naïve CD8 T cell IFN-γ responses to T. gondii require the inflammasome-independent NLRP3 pathway and rhoptry proteins (ROP) 5 ( 59 ). This paper was identified that the NLRP3 regulates T cell function and underscore the need for NLRP3-activating adjuvants in vaccines targeted at inducing CD8 T cell-derived IFN-γ responses to T. gondii .…”
Section: Functions Of Inflammasomes In Rodent Models Of T mentioning
confidence: 99%
“…Bone marrow derived macrophages (BMDMs) were generated as previously described [ 26 ], and plated on coverslips in 24 well plates in medium (4.5 g/liter D-glucose DMEM with GlutaMAX (Gibco), 10% heat-inactivated FBS, 1% penicillin-streptomycin (Gibco), 1X non-essential amino acids (Gibco, cat# 11140076), 1mM sodium pyruvate (Gibco, cat# 11360070)) supplemented with 10% L929 conditioned medium and incubated overnight 37°C, 5% CO 2 . Heat-inactivated blood plasma was used to coat live GFP+ parasites for 20 minutes at 37°C before infecting at a multiplicity of infection of 0.2.…”
Section: Methodsmentioning
confidence: 99%
“…“superinfect”) the brains of challenged survivors [ 25 ]. Vaccinated C57BL/6J mice are also susceptible to challenge with homologous strains, suggesting that defects in antigen recognition cannot fully explain immune failure to clear virulent strains [ 25 , 26 ]. During secondary infection memory CD8 T cells become exhausted, but checkpoint blockade fails to reverse disease outcome [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation